Study of Recurrent Laryngeal Nerve Paralysis Following Thyroidectomy - Md Wahiduzzaman, -; Razib, Syed Farhan Ali; Hossain, Afroja; Rahman, Sheikh Hasanur; Rahman, Hasib; Haque, Md Hasanul; Tarafder, Kamrul Hasan (Bangladesh Journal of Otorhinolaryngology, 2019)
Abstract not available Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 162-166